2014
DOI: 10.1002/ajhb.22530
|View full text |Cite
|
Sign up to set email alerts
|

Symptom perception in healthy menopausal women: Can we predict concordance between subjective and physiological measures of vasomotor symptoms?

Abstract: Just over one third of physiologically recorded HF/NS were perceived as hot flushes; under-reporting of symptoms was more common than over-reporting. Interestingly, women who were more accurate in detecting physiological HF/NS tended to report more psychological and somatic symptoms and negative beliefs about HF/NS. Both measures should be included as outcomes of clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The reasons for this association are unclear. Smoking is a risk factor for experiencing HFs[ 24 , 32 ] and smokers tend to over-report the frequency of their hot flashes[ 33 ], rate their hot flashes as more problematic[ 34 ] and report higher levels of bother from their hot flashes than non-smokers with a similar HF burden[ 35 ]. This finding should be interpreted with caution as the proportion of smokers in our study was small.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this association are unclear. Smoking is a risk factor for experiencing HFs[ 24 , 32 ] and smokers tend to over-report the frequency of their hot flashes[ 33 ], rate their hot flashes as more problematic[ 34 ] and report higher levels of bother from their hot flashes than non-smokers with a similar HF burden[ 35 ]. This finding should be interpreted with caution as the proportion of smokers in our study was small.…”
Section: Discussionmentioning
confidence: 99%
“…Increased skin conductance is an objective marker of sweating which occurs in menopausal flushing. Sternal skin conductance (SSC) was measured using a previously described Bahr hot flush monitor that measured SSC in microsiemens (μS) every 10 seconds by passing an electric current across two electrodes attached to the sternal region of the chest (Simplex Scientific, Wisconsin, USA) 19 24 25 .…”
Section: Methodsmentioning
confidence: 99%
“…In another study, these same investigators found that more perceived self-control on hot flushes and night sweats was associated with less severe vasomotor symptoms [11]. A prospective study among women with moderate to severe hot flushes and night sweats reported that negative beliefs about night sweats and sleep were the strongest predictors of concordance between objective and subjective measures of these symptoms [12]. All these studies focused either on lifestyle or psychological variables; none included potential biologic predictors of symptom severity.…”
Section: Introductionmentioning
confidence: 99%